Snail Mediates E-Cadherin Repression by the Recruitment of the Sin3A/Histone Deacetylase 1 (HDAC1)/HDAC2 Complex - Peinado, Hector (American Society for Microbiology, 2004)
The transcription factor Snail has been described as a direct repressor of E-cadherin expression during development and carcinogenesis; however, the specific mechanisms involved in this process remain largely unknown. Here we show that mammalian Snail requires histone deacetylase (HDAC) activity to repress E-cadherin promoter and that treatment with trichostatin A (TSA) is sufficient to block the repressor effect of Snail. Moreover, overexpression of Snail is correlated with deacetylation of histones H3 and H4 at the E-cadherin promoter, and TSA treatment in Snail-expressing cells reverses the acetylation status of histones. Additionally, we demonstrate that Snail interacts in vivo with the E-cadherin promoter and recruits HDAC activity. Most importantly, we demonstrate an interaction between Snail, histone deacetylase 1 (HDAC1) and HDAC2, and the corepressor mSin3A. This interaction is dependent on the SNAG domain of Snail, indicating that the Snail transcription factor mediates the repression by recruitment of chromatin-modifying activities, forming a multimolecular complex to repress E-cadherin expression. Our results establish a direct causal relationship between Snail-dependent repression of E-cadherin and the modification of chromatin at its promoter.